Rusçuk Çiftlikleri ve Çiftlik Piyasasında Eski Aktörler, Yeni Figürler - Ahmet İlker BAŞ (Gazi Akademik Bakış)
Çiftlik is the one of the most important debate topics in Ottoman agricultural history. While they are generally evaluated under the topics of landownership and legal status of peasants in the context of centrifugal forces, as a commodity, the exchange of çiftliks in the real estate market does not attract scholars’ attention enough. Data extracted from sale contracts in the kadı records enable researchers to track changes in the profiles of çiftlik sellers and buyers in a period of commercialization of agriculture. Learning what kind of socio-economic and political capital owners are more interested in çiftliks ownership through honorific titles and elkâbs helps to comprehend at least one dimension of transformation of Ottoman provinces in 17th and 18th centuries. This article aims to describe the structure of çiftliks and their productive activities on the one hand, and on the other, to determine the motivations effective in çiftlik sales by using sale contracts along with inheritance records. Thus, the reflection of the relationship correlated between proliferation of çiftliks and rise of the local notables to the çiftlik market can be traced. Therefore, çiftlik sale contracts have the potential to add a new perspective to çiftlik debates.